DIGITAL LITERACY AS A SCHOOL COUNSELOR COMPETENCE IN THE DEVELOPMENT OF MEDIA IN GUIDANCE SERVICES - Andre Julius; Irfan Fahriza; Praditha Wulandari (Jurnal Penelitian Bimbingan dan Konseling, 2020)
Ease of access to technology tools is an opportunity for school counsellors to develop diverse and interesting media guidance services. But if the counsellor does not have digital literacy capabilities, the service of media development can become irrelevant, obsolete, and abandoned. This literature review aims to illustrate the importance of digital literacy as a school counsellor competency, as well as outlining aspects of digital literacy in media development. The study uses textbooks, research journals, and community service report as an analysis of the application of digital literacy to educational practices. Based on this study, school counsellors are required to be able to process and evaluate digital information/data and create digital products that are more relevant to learners. Digital literacy competencies consist of 1) underpinning,  2) background knowledge, 3) central competencies, 4) attitudes, and perspectives. The key to this competency is critical thinking,  and school counsellors can get used to brainstorming to practice it.  Keywords: Digital Literacy, Media, Guidance and Counseling